Description of Two New Species of Philometra Costa, 1845 (Nematoda: Philometridae) from Marine Fishes off Japan, with Notes on Philometroides seriolae (Yamaguti, 1935) - Moravec, František; Ogawa, Kazuo (Acta parasitologica, 2019)
PURPOSE: Philometrid nematodes (Philometridae) represent a group of more than 200 species parasitic in the body cavity and various body tissues of fishes. Due to morphological and biological peculiarities, the majority of them are known only by their large females. Generally, the fauna of these parasites remains little known. METHODS: Occasional helminthological examinations of three species of marine fishes in Japan revealed two new and one insufficiently known species of these tissue-dwelling parasites. These were studied with the use of light and scanning electron microscopy. RESULTS: All three nematode species are described. Philometra ostorhinchi sp. nov. (males and females) from the ovary of Ostorhinchus semilineatus (Temminck et Schlegel) (Apogonidae, Perciformes) is characterized mainly by the lengths and structure of spicules and the gubernaculum (spicules 108-120 µm long, length of the gubernaculum 78-87 µm); it is the only species of philometrids parasitic in a fish belonging to the Apogonidae. The gravid females of Philometra tenuis sp. nov. (only females available) from the head subcutaneous tissues of Conger myriaster (Brevoort) (Congridae, Anguilliformes) differ from congeners mainly in an unusual shape of the anterior oesophageal bulb. Some new data on the morphology of an insufficiently known species Philometroides seriolae (Ishii, 1931), collected from the body musculature of Seriola quinqueradiata Temminck et Schlegel (Carangidae, Perciformes), are provided; the number and arrangement of cephalic papillae in subgravid females of P. seriolae were found to be similar to those in females of the majority of other philometrid species. CONCLUSIONS: The present study extends the knowledge of the species composition of philometrids parasitizing marine fishes and of the morphology of P. seriolae, the type species of Philometroides Yamaguti, 1935.
Keywords: Animals; ovarium; Female; ženské pohlaví; Perciformes; druhová specificita; nemoci ryb; New taxa; Fish Diseases; Fishes; Dracunculoidea; Oceans and Seas; pohlavní orgány; Species Specificity; West Pacific Ocean; oceány a moře; Japonsko; ryby; Japan; Male; Ovary; zvířata; mužské pohlaví; mikroskopie; Anguilliformes; Microscopy; Genitalia